Kinematic relevance of short approach jumps as a training tool for competition long jumping - Shin, C.; Allen, S.; Brice, P. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Training for the long jump involves short approach jumps which are often assumed to replicate full approach jump take-off. The aim of this study was to compare directly the kinematics of short and full approach jumps. One elite female long jumper completed seven 10 step approach jumps during one training session, and five full approach jumps in an international competition. Video from a fixed camera was digitised and kinematic variables for the final touchdown calculated. Approach run step kinematics were obtained from a panning camera. Statistically significant (p < 0.05) differences were identified in approach step characteristics and in horizontal velocity, but none were found in vertical velocity generated. Results indicate short approach jumps are a useful tool for generation of vertical velocity but do not directly replicate full approach jumps in approach or take off.